Segment disclosure pratices and determinants: Evidence from Romanian listed companies - Ruxandra-Adriana Mateescu (The International Journal of Management Science and Information Technology (IJMSIT), 2016)
This paper aims to be a theoretical but also an empirical study regarding the way listed companies in Romania comply with the requirements of IFRS 8 'Operating Segments', assessing which is the information companies usually disclose about their operating segments. The second part of the study is dedicated to studying the factors which determine companies to disclose high quality segment information, particular attention is being paid to assessing to what extent does an independently structured board influence the quality of segment reporting or if there are more powerful internal factors that influence the way companies implement this reporting standard.
Keywords: 650; Boards' independence; institutional investors; Romanian listed companies; Segment reporting